IDNLearn.com offers expert insights and community wisdom to answer your queries. Get prompt and accurate answers to your questions from our experts who are always ready to help.
Sagot :
Answer:
p = 11 q = 3
Step-by-step explanation:
2p - 3q = 13
- p - 3q = 2
p = 11
p - 3q = 2
(11) - 3q = 2
-3q = -9
q = 3
Answer:
p=11 q=3
Step-by-step explanation:
subtract second from first
2p-3q=13
-p+3q=-2
p=11
plug in
11-3q=2
-3q=-9
q=3
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! Discover the answers you need at IDNLearn.com. Thank you for visiting, and we hope to see you again for more solutions.